2010
DOI: 10.1111/j.1651-2227.2009.01573.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term effects of rapid weight gain in children, adolescents and young adults with appropriate birth weight for gestational age: the kiel obesity prevention study

Abstract: Rapid weight gain was related to increases in height, weight, a higher prevalence of overweight and central fat distribution. In addition, rapid weight gain was related to a higher REE in boys, but not to cardio-metabolic risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 28 publications
(43 reference statements)
0
12
0
Order By: Relevance
“…There is substantial evidence that obesity risk may begin very early in life; > 40 studies have documented rapid weight gain in the first few months after birth to be associated with obesity later in life (Akaboshi et al 2008; Blair et al 2007; Botton et al 2008; Chomtho et al 2009; Demerath et al 2009; Dubois and Girard 2006; Durmuş et al 2010; Ekelund et al 2006; Eriksson et al 2008; Goodell et al 2009; Hitze et al 2010; Kain et al 2009; Karaolis-Danckert et al 2006; Lamb et al 2010; Ong and Loos 2006; Ong et al 2009; Taveras et al 2009; Toschke et al 2004) or related metabolic disorders (Cournil et al 2009; EURODIAB Substudy 2 Study Group 2002; Harder et al 2009; Huxley et al 2000; Law et al 2002; Leunissen et al 2009). Although feeding practices likely play a role (Koletzko et al 2009; Worobey et al 2009), there is considerable uncertainty regarding other factors that may program this rapid infant growth.…”
mentioning
confidence: 99%
“…There is substantial evidence that obesity risk may begin very early in life; > 40 studies have documented rapid weight gain in the first few months after birth to be associated with obesity later in life (Akaboshi et al 2008; Blair et al 2007; Botton et al 2008; Chomtho et al 2009; Demerath et al 2009; Dubois and Girard 2006; Durmuş et al 2010; Ekelund et al 2006; Eriksson et al 2008; Goodell et al 2009; Hitze et al 2010; Kain et al 2009; Karaolis-Danckert et al 2006; Lamb et al 2010; Ong and Loos 2006; Ong et al 2009; Taveras et al 2009; Toschke et al 2004) or related metabolic disorders (Cournil et al 2009; EURODIAB Substudy 2 Study Group 2002; Harder et al 2009; Huxley et al 2000; Law et al 2002; Leunissen et al 2009). Although feeding practices likely play a role (Koletzko et al 2009; Worobey et al 2009), there is considerable uncertainty regarding other factors that may program this rapid infant growth.…”
mentioning
confidence: 99%
“…To better understand the relationships between prenatal growth and obesity, future studies should consistently measure prenatal growth by gestational age, as has also been previously recommended. 22,56 Studies that use other proxies, such as birthweight, should be very clear about what such a measure can and cannot tell us about prenatal growth. Lack of standard terminology is a major concern: several studies used the same terms for different measures of postnatal growth and others used different terms for the same measure.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18] Studies have also indicated that postnatal growth during the first 1-2 years of life may be positively associated with subsequent obesity in childhood, adolescence and adulthood, as obesity risks, both in terms of body mass index (BMI) and adverse body composition, are higher for those who experienced rapid postnatal weight gain. [19][20][21][22][23] An important consideration in understanding the early life emergence of obesity risks is the relationship between prenatal and postnatal growth and whether some combinations of growth increase risks. Prenatal growth has been shown to be inversely associated with postnatal growth, with babies born smaller experiencing higher growth during infancy compared with larger babies.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was observed that as birth weight decreased, proportionately more subcutaneous fat was accumulated in the body among children aged 7-12 years [14]. Notably, it was recently published that different birth-weight categories could influence the prevalence of obesity during childhood [28] and high rapid weight gain in the first year of life could be an important predictor of obesity status in low-birth-weight preterm infants [28,33,34,35], or in post-term [36] or term-birth children [37]. Likewise, considering a genetic trait, it was observed that functional -243 A→G polymorphism in the 5′ promoter region of glutamic acid decarboxylase 2 (GAD2) genes could result in decreasing insulin resistance and influence feeding behavior, which could be an important determinant of subsequent risk of obesity among low-birth-weight children [7].…”
Section: Discussionmentioning
confidence: 99%